HUBUNGAN BERAT BAYI DENGAN ROBEKAN PERINEUM PADA PERSALINAN FISIOLOGIS DI RB LILIK SIDOARJO - Dwi Anggraini, Fritria (Jurnal Ilmiah Kesehatan, 2016)
the relationship with birth weight at delivery perineal robekan in RB Lilik. Childbirth often results in injury or birth canal called the perineal robekan, birth weight effect on stretching the perineum, but the robekan perenium still occur despite the child born today is not too large. The purpose of this study to analyze the relationship with birth weight at delivery perineal robekan in RB Lilik .Research design was analytic: cross sectional. The population were the entire maternal physiological in BPS Lilik Farida Kedurus Sidoarjo in June 2013 by 27 people then. Sample were 25 responden. The independent variable birth weight and the dependent variable robekan of the perineum. Sampling technique performed probability sampling with simple random sampling technique. Data were analyzed using the Mann-whtney statistical test using SPSS for Windows and the level of significance ? = 0.05. Results of Mann-Whitney statistical test showed ? = 0.004 means that there is a relationship between birth weight with perineal robekan at physiological childbirth. Conclusions delivery with birth weight effect on stretching the perineum which can lead to robekan of the perineum.